2015
DOI: 10.1021/acs.analchem.5b00890
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Impedimetric Aptasensor for Ochratoxin-A Detection Using Iridium Oxide Nanoparticles

Abstract: In this article, a novel aptasensor for ochratoxin A (OTA) detection based on a screen-printed carbon electrode (SPCE) modified with polythionine (PTH) and iridium oxide nanoparticles (IrO2 NPs) is presented. The electrotransducer surface is modified with an electropolymerized film of PTH followed by the assembly of IrO2 NPs on which the aminated aptamer selective to OTA is exchanged with the citrate ions surrounding IrO2 NPs via electrostatic interactions with the same surface. Electrochemical impedance spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
88
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(88 citation statements)
references
References 36 publications
(55 reference statements)
0
88
0
Order By: Relevance
“…As a result, the R TC of the electrode (given by the diameter of the semicircle as indicated in Figure 4), monitored upon immersing the immunosensor into a [Fe(CN) 6 ] 3−/4− solution, decreased with increasing OTA concentration within a dynamic range of 0.1 pg·mL −1 -30 ng·mL −1 . The developed method was successfully used for the determination of OTA in red wine samples where the maximum permitted level of toxin is 2 µg·kg −1 [65]. Good recoveries were obtained in the analysis of samples spiked with OTA at different concentration levels ranging between 5 pg·mL −1 and 10 ng·mL −1 [63].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…As a result, the R TC of the electrode (given by the diameter of the semicircle as indicated in Figure 4), monitored upon immersing the immunosensor into a [Fe(CN) 6 ] 3−/4− solution, decreased with increasing OTA concentration within a dynamic range of 0.1 pg·mL −1 -30 ng·mL −1 . The developed method was successfully used for the determination of OTA in red wine samples where the maximum permitted level of toxin is 2 µg·kg −1 [65]. Good recoveries were obtained in the analysis of samples spiked with OTA at different concentration levels ranging between 5 pg·mL −1 and 10 ng·mL −1 [63].…”
Section: Introductionmentioning
confidence: 96%
“…In addition, it was successfully applied to the determination of in cereal samples. An original impedimetric immunosensor for the fast determination of OTA in food samples was recently developed using signal tags by co-immobilization of anti-OTA antibody and amine-terminated dendrimer (PAMAM) onto graphene oxide nanosheets and also combining [65]. Good recoveries were obtained in the analysis of samples spiked with OTA at different concentration levels ranging between 5 pg·mL −1 and 10 ng·mL −1 [63].…”
Section: Introductionmentioning
confidence: 99%
“…Despite of their improved analytical merits, antibodies are considered very expensive bio-recognition element with problem of long term stability, in addition to being produced by the animal source. Aptamers are an emerging class of synthetic molecules for biomolecular recognition which offers several advantages compared to antibodies, including their high affinity and specificity for a wide range of targets, thermal and chemical stability, and low-cost production [11]. Moreover, they have a longer shelf life than antibodies, are resistant to repetitive cycles of denaturation/renaturation and are less prone to degradation [12].…”
Section: Introductionmentioning
confidence: 99%
“…for detection of copper(Chen et al 2011) and acetamiprid. A study carried out byRivas et al (2015) demonstrated the use of iridium oxide nanoparticles for coating screen printed carbon electrodes. The aptamers were conjugated to the NPs to achieve highly sensitive impedimetric detection of OTA in wine samples.Often adsorption of non-specific DNA to the surface of electrodes can lead to false results.…”
mentioning
confidence: 99%